Símbolos de Imbituba/SC: análise comparativa entre o brasão do município e o imaginário das crianças das escolas municipais - Aviz, Emanuelle Querino Alves (2019)
This thesis has as its theme the comparative analysis between the Coat of Arms of the Municipality of Imbituba and the children’s Imaginary of the municipal schools. The coat of arms, established in 1970, is the main imaging element of municipal communication and presents figures that record part of the city's history. The objective was to find out if the children's imaginary continues to be fed by the same imaginary that inspired it, from the identification of schèmes, archetypes, symbols and myths, as well as the Daytime and Night-time Regimes of the image (DURAND, 2001). As a methodology for the application of the research, we used the culturanalysis of groups (PAULA CARVALHO, 1989, 1998 and 1999) with a myth criticism analysis (DURAND 1985, 1996, 2011). The results indicate that the children's imaginary reflects in parts the imagery of the Coat of Arms, but it is also permeated by other influences, indicating a phase change in the semantic basin. The main myth found is that of Dionysus, with relations to the myths of the Minotaur and Icarus.